Simulating the efficient diffusion of photovoltaics in Bogotá: An urban metabolism approach. (15th March 2020) - Rúa, Diego; Castaneda, Monica; Zapata, Sebastian; Dyner, Isaac
Abstract: Urban metabolism has proven to be suitable for assessing the environmental performance of cities. Bogotá, one of the world's highest-located and largest tropical cities, has made little use of rooftop photovoltaics, despite its potential. Using a simulation model, based on the urban metabolism approach, this paper examines several possible PV technology diffusion paths considering the consumer adoption processes of the residential, commercial, industrial and institutional sectors of the city. Further, the impact of PV diffusion is analyzed in terms of urban metabolism indicators such as greenhouse gas emissions and reduction of technical losses in the electricity system. Results indicate that policy is required for promoting consumer awareness about the use of PVs for meeting electricity demand. Reductions in greenhouse gas emissions of up to 820, 000t of CO2 per year could be achieved. Adoption rates in the residential sector of the order of 26% could be possible. This in turn would represent an installed capacity of 1.5 GW, and emission reductions of 450, 000t of CO2 per year. Additionally, the commercial sector could reach a potential installed capacity of 1.2 GW. The industrial and institutional sectors could reach an installed capacity of about 10 MW and 70 MW respectively. Highlights: A simulation model was constructed to study the diffusion of photovoltaics in Bogotá. The model considers CO2 emissions, electricity losses and photovoltaics installed capacity. The paper identifies opportunities for developing solar photovoltaics in Bogotá. Policy contributes for attaining the efficient penetration of photovoltaics.